PENGARUH MEDIA SOSIAL TERHADAP KEHIDUPAN SOSIAL REMAJA: ANALISIS DAMPAK PENGGUNAAN PLATFORM DIGITAL DALAM INTERAKSI SOSIAL - Tania Yulianisa; Desy Safitri; Sujarwo Sujarwo (KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the influence of social media on adolescents’ social lives, especially its effects on friendship quality, social connectedness, face-to-face interaction, identity development, and peer pressure. Social media platforms have become daily communication spaces where adolescents maintain relationships, seek support, express themselves, and join wider communities. This article uses a descriptive qualitative literature review by synthesizing ten publications and official reports issued between 2021 and 2025. The selected sources include longitudinal studies, ecological momentary assessments, correlational research, qualitative studies, and systematic reviews. The findings show that social media does not produce a single uniform effect. Active and purposeful communication can strengthen existing friendships, provide emotional support, expand social networks, and help adolescents explore identity. In contrast, passive browsing, excessive use, social comparison, continuous peer monitoring, and pressure to remain constantly connected can reduce perceived connectedness, increase loneliness, intensify interpersonal conflict, and encourage problematic use. Offline friendship quality remains a strong protective factor. The impact also differs according to gender, self-esteem, self-concept clarity, peer susceptibility, motives for use, and the type of platform activity. The study concludes that adolescents need balanced digital habits, critical media literacy, clear interpersonal boundaries, and continued face-to-face interaction, Families and schools should guide social media use without ignoring its role as a legitimate social environment for adolescents.